Contribution to the production and use of biomass-derived solvents : a review - Kochepka, Débora Merediane (2020)
ABSTRACT: In this review key processes for the synthesis of greener or more sustainable solvents derived from renewable sources (saccharides, lignocellulose and triglycerides) are discussed. It is shown that a series of platform chemicals such as glycerol, levulinic acid and furans can be converted into a variety of solvents through catalytic transformations that include hydrolysis, esterification, reduction and etherification reactions. It was also considered several aspects of each class of solvent regarding performance within the context of the reactions or extractions for which it is employed.